1979
DOI: 10.1085/jgp.74.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Ionic and osmotic equilibria of human red blood cells treated with nystatin.

Abstract: Human red blood cells have been incubated in the presence of nystatin, which allows Na and K, as well as CI and pH to equilibrate rapidly when cell volume is set with external impermeant sucrose. The intracellular mean ionic activity coefficients, relative to values in the extraceUular solution, for KCI and NaCl are 1.01 4" 0.02 and 0.99 + 0.02 (SD, n = 10), respectively, and are independent of external pH, pH o, and of [sucrose]o. With nystatin the dependence of red cell volume on [sucrose]~ deviates from ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(115 citation statements)
references
References 46 publications
6
109
0
Order By: Relevance
“…As discussed above and elsewhere (Siebens, 1985), these changes in Vm can be accounted for by changes in the relative contribution of the impermeant anions to the membrane potential . If this is true, it should be possible in future studies to use nystatin to make Amphiuma red cells permeable to cations and anions (Dalmark, 1975 ;Freedman and Hoffman, 1979) and to obtain values of rCl as a function of volume similar to those of the present study.…”
Section: Movements and Distributionssupporting
confidence: 55%
See 1 more Smart Citation
“…As discussed above and elsewhere (Siebens, 1985), these changes in Vm can be accounted for by changes in the relative contribution of the impermeant anions to the membrane potential . If this is true, it should be possible in future studies to use nystatin to make Amphiuma red cells permeable to cations and anions (Dalmark, 1975 ;Freedman and Hoffman, 1979) and to obtain values of rCl as a function of volume similar to those of the present study.…”
Section: Movements and Distributionssupporting
confidence: 55%
“…Because the osmotic coefficient of mammalian hemoglobin is known to change as a function of concentration (Adair, 1929;Dick and Lowenstein, 1958 ;McConaghey and Maizels, 1961 ;Freedman and Hoffman, 1979), the predicted value of aapp is actually expected to be slightly greater than the medium osmolality in the VRD and VRI responses because of changes in the osmotic coefficient of hemoglobin during volume recovery (Siebens, 1985). In the Amphiuma red cell, this slight effect predicts that a.pp will be^-6 and 13 mosmol hypertonic to the medium in the VRD and VRI responses, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…The latter assumption is not expect to lead to a considerable mistake, insofar as the modeling of the intracellular phase as a diluted electrolyte solution is found to give correct predictions about the concentrations of ions due to inorganic electrolytes, such as K + , Na + , Cl − , etc. [52].…”
Section: Expressions For the Electric Potentialmentioning
confidence: 99%
“…Jeffrey Freedman designed and executed studies concerned with the conditions that account for ionic equilibrium of human red blood cells (86). Jeffrey showed that the charge of Hb was independent of its concentration and more importantly that evaluation of the ionic activity coefficients of Na + , K + , and Cl − and the osmotic coefficient of Hb, as a function of concentration, could quantitatively describe the dependence of the Donnan ratios and cell volumes on the ionic composition of the medium and its pH (86).…”
Section: Nab-ouabain: 2-nitro-5-azidobenzoyl Ouabainmentioning
confidence: 99%
“…Jeffrey showed that the charge of Hb was independent of its concentration and more importantly that evaluation of the ionic activity coefficients of Na + , K + , and Cl − and the osmotic coefficient of Hb, as a function of concentration, could quantitatively describe the dependence of the Donnan ratios and cell volumes on the ionic composition of the medium and its pH (86). The analysis also corrected Ponder's "R" value (26) ++ on either the activation of the Gárdos channel or the inhibition of the Na + pump.…”
Section: Nab-ouabain: 2-nitro-5-azidobenzoyl Ouabainmentioning
confidence: 99%